Ultrafine MoS2 Nanosheets Vertically Patterned on Graphene for High-Efficient Li-Ion and Na-Ion Storage - Wei, Chunguang; Hou, Zhidong; Sun, Huanhuan; Wang, Jian-Gan (Frontiers in Chemistry, 2021)
Hierarchically two-dimensional (2D) heteroarchitecture with ultrafine MoS2 nanosheets vertically patterned on graphene is developed by using a facile solvothermal method. It is revealed that the strong interfacial interaction between acidic Mo precursors and graphene oxides allows for uniform and tight alignment of edge-oriented MoS2 nanosheets on planar graphene. The unique sheet-on-sheet architecture is of grand advantage in synergistically utilizing the highly conductive graphene and the electroactive MoS2, thus rendering boosted reaction kinetics and robust structural integrity for energy storage. Consequently, the heterostructured MoS2@graphene exhibits impressive Li/Na-ion storage properties, including high-capacity delivery and superior rate/cycling capability. The present study will provide a positive impetus on rational design of 2D metal sulfide/graphene composites as advanced electrode materials for high-efficient alkali–metal ion storage.